1974
DOI: 10.1037/h0036750
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of highlighting for retention of text material.

Abstract: The effectiveness of "highlighting" selected text material for improving retention was examined in 4 groups of 19 college students each. Although there were no differences among the groups in total score on a retention test one week after reading with different highlighting techniques or no highlighting, a detailed analysis implied that highlighting improves retention of selected text material and that active highlighting is superior to passive reading of highlighted material. Highlighting seemed most effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
0
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(85 citation statements)
references
References 11 publications
6
77
0
2
Order By: Relevance
“…For instance, although studying with friends may have some benefits, students may not always collaborate appropriately when studying together. Also, highlighting by a textbook publisher or instructor can improve performance, but students' use of highlighting has been shown to yield mixed results, depending on the skill of the user (e.g., Bell & Limber, 2010;Fowler & Barker, 1974). Thus, at least some of these strategies may actually be relatively inert when used by typical students.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, although studying with friends may have some benefits, students may not always collaborate appropriately when studying together. Also, highlighting by a textbook publisher or instructor can improve performance, but students' use of highlighting has been shown to yield mixed results, depending on the skill of the user (e.g., Bell & Limber, 2010;Fowler & Barker, 1974). Thus, at least some of these strategies may actually be relatively inert when used by typical students.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies on text comprehension that have used memory performance (i.e., recall) as an indicator of attentional processing have consistently shown that cues improve the recall of the content they emphasize (Cashen and Leicht 1970;Dee-Lucas and DiVesta 1980;Fowler and Barker 1974;Hartley and Trueman 1985;Lorch and Lorch 1996). Memory for uncued content is unaffected (Foster 1979;Golding and Fowler 1992), inhibited (Glynn and DiVesta 1979), or sometimes even enhanced (Cashen and Leicht 1970).…”
Section: Guiding Attention To Essential Informationmentioning
confidence: 99%
“…The few studies conducted from the perspective of a subsequent reader have focused on the effects of annotations upon recall. These studies generally conclude that reading texts that have been highlighted by expert readers improves recall on the emphasized items [3,4,7,20].…”
Section: Introductionmentioning
confidence: 99%